Interleukin-10 Polymorphisms in Association with Prognosis in Patients with B-Cell Lymphoma Treated by R-CHOP - Min Kyeong Kim; Kyong-Ah Yoon; Eun Young Park; Jungnam Joo; Eun Young Lee; Hyeon-Seok Eom; Sun-Young Kong (Genomics & Informatics)
Interleukin-10 (IL10) plays an important role in initiating and maintaining an appropriate immune response to non-Hodgkin lymphoma (NHL). Previous studies have revealed that the transcription of IL10 mRNA and its protein expression may be infl uenced by several single-nucleotide polymorphisms in the promoter and intron regions, including rs1800896, rs1800871, and rs1800872. However, the impact of polymorphisms of the IL10 gene on NHL prognosis has not been fully elucidated. Here, we investigated the association between IL10 polymorphisms and NHL prognosis. This study involved 112 NHL patients treated at the National Cancer Center, Korea. The median age was 57 years, and 70 patients (62.5%) were men. Clinical characteristics, including age, performance status, stage, and extra-nodal involvement, as well as cell lineage and International Prognostic Index (IPI), were evaluated. A total of four polymorphisms in IL10 with heterozygous alleles were analyzed for hazard ratios of overall survival (OS) and progression-free survival (PFS) using Cox proportional hazards regression analysis. Diffuse large B-cell lymphoma was the most common histologic type (n = 83), followed by T-cell lymphoma (n = 18), mantle cell lymphoma (n = 6), and others (n = 5). Cell lineage, IPI, and extra-nodal involvement were predictors of prognosis. In the additive genetic model results for each IL10 polymorphism, the rs1800871 and rs1800872 polymorphisms represented a marginal association with OS (p = 0.09 and p = 0.06) and PFS (p = 0.05 and p = 0.08) in B-cell lymphoma patients treated with rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP). These findings suggest that IL10 polymorphisms might be prognostic indicators for patients with B-cell NHL treated with R-CHOP.